(untitled) (Journal of Economic Research & Business Administration, 2016)
The article is concerned with problems of normative determination of subjects of public control in the context of discussion of different options of project of Law of the Republic of Kazakhstan “About public control”. The author’s interpretation of meaning “public control” is proved. Inter-relation of “Third Sector” and phenomenon of public control is identified. General global trends and contradictions of development of structures of NGO are shown. It is proved that Kazakhstani legislator should reject of-fers of some Kazakhstani social organizations about normative consolida-tions in the Law of the Republic of Kazakhstan “About public control” of public at large and structure of NGO as subjects of public control. Charac-teristic features of processing of social transformation of Kazakhstani soci-ety are determined and necessity of accent passage in activity of subjects of public control with traditional problems of additional control for activity of state and business structures for system organization of quality control of services of NGO.